Design of four-point SENB specimens with stable crack growth. (15th March 2018) - Jørgensen, Jeppe B.; Kildegaard, Casper; Sørensen, Bent F.
Highlights: The homogenous four-point SENB specimen loaded by fixed grip is modeled analytically. The bi-material four-point SENB specimen loaded by fixed grip is modeled numerically. Stable crack propagation was measured on experimental tests. Prediction of stable crack propagation was found to agree well with measurements. Abstract: A four-point single-edge-notch-beam (SENB) test specimen loaded in displacement control (fixed grip) is proposed for studying crack deflection at bi-material interfaces. In order to ensure stable crack growth, a novel analytical model of the four-point SENB specimen in fixed grip is derived and compared with numerical models. Model results show that the specimen should be short and thick, and the start-crack length should be deep for the crack to propagate stable towards the bi-material interface. Observations from experimental tests of four-point SENB specimens with different start-crack lengths, confirmed that the crack grows stable if the start-crack length is deep and unstable if not.